(untitled) (Indonesian Journal of Primatology, 2024)
Early diagnosis of Alzheimer’s is still difficult to do, thus it is important to carry out further research to find biomarkers that can be used to detect early Alzheimer’s disease. Proliferating Cell Nuclear Antigen (PCNA) is known as a proliferation marker, which has the potential to detect neurogenesis in the brain. This study aimed to identify PCNA gene expression in the brain as a marker of Alzheimer’s disease in Macaca fascicularis. Macaca fascicularis was used in this study because of their similarities with humans in terms of their behavioral complexity, as well as high cognitive abilities and the formation of a pathological characteristic of Alzheimer’s disease in the brain. This study used the brains of 7 monkeys in the hippocampus and cortical regions. Monkeys previously have been divided into old and adult age groups. The detection of PCNA gene expression was done using RT-qPCR method. The results showed the gene expression tended to be higher in the adult group and the hippocampus region, although based on statistical analysis showed no significant differences